Essence and features musical perception of pupils in music (Pedagogy of Higher and Secondary Education, 2013)
Furdak T. D. Essence and features musical perception of pupils in music.The article thoroughly essence and features musical perception by pupils for music lessons. Based on the theoretical analysis of the investigations, experience university professors and teachers of music schools offer stages of the process ability to consciously perceive music students.
Keywords: musical perception; emotional and conscious perception; cognition; cognitive interest